Perbandingan adat istiadat kesultanan Melayu-Jepun berdasarkan naskhah klasik - Jelani Harun, 1962- (Dewan Bahasa dan Pustaka, 2010)
Cross-cultural study on social life and customs of Malay sultanates and the Japanese monarchy according to classical manuscripts; comparative literature.